2018
DOI: 10.1038/s41467-018-06742-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural delineation of potent transmission-blocking epitope I on malaria antigen Pfs48/45

Abstract: Interventions that can block the transmission of malaria-causing Plasmodium falciparum (Pf) between the human host and Anopheles vector have the potential to reduce the incidence of malaria. Pfs48/45 is a gametocyte surface protein critical for parasite development and transmission, and its targeting by monoclonal antibody (mAb) 85RF45.1 leads to the potent reduction of parasite transmission. Here, we reveal how the Pfs48/45 6C domain adopts a (SAG1)-related-sequence (SRS) fold. We structurally delineate poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 58 publications
(62 reference statements)
0
81
1
Order By: Relevance
“…On the other hand, N299 was found not to be glycosylated with the side chain of N299 involved in H bonding with S301. These two N-glycosylation sites (N299 and N303) are not directly involved in the binding of 6C to 85RF45.1, but the results reported here, together with Kundu et al, suggest that amino acid sequence at these sites can play important roles in the proper folding of 6C 16 . While the glycosylation at these sites are not expected to occur in the parasite, our results also suggest that mutation of the primary sequence may also disturb higher order structure.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…On the other hand, N299 was found not to be glycosylated with the side chain of N299 involved in H bonding with S301. These two N-glycosylation sites (N299 and N303) are not directly involved in the binding of 6C to 85RF45.1, but the results reported here, together with Kundu et al, suggest that amino acid sequence at these sites can play important roles in the proper folding of 6C 16 . While the glycosylation at these sites are not expected to occur in the parasite, our results also suggest that mutation of the primary sequence may also disturb higher order structure.…”
Section: Discussioncontrasting
confidence: 47%
“…In recent studies, Kundu et al cloned the 6C fragment in HEK 293 cells without genetic modification of the N-glycosylation sites, N299 and N303, and the resulting crystal structure revealed that N303 is indeed 16 . After EndoH treatment, the N-acetylglucosamine attached to N303 forms H-bonds with D390 and D391 of the 6C molecule.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main features of the SpyTag/SpyCatcher technology is the possibility to orientate the antigen on the VLP surface to expose the functional epitopes, which leads to the generation of a better quality of response (22). Recent progresses in the malaria-TBV field unrevealed structures and mapped epitopes of important antigen candidates that had remained elusive for long time (42)(43)(44). The combination of the new insights into the structure of these antigens, including Pfs25, and the possibility to specifically orientate them on HBsAg::SpyCatcher, offers a unique advantage in the design of novel vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Within this family of Pfs230-like proteins, structures have been resolved for two members, which form a complex with an unknown function, Pf12 17 , 18 and Pf41 19 . Recently, the carboxyl-terminal cysteine-rich domain of Pfs48/45, identified as 6C, was cocrystalized with a TB mAb, which may aid in future vaccine design of a Pfs48/45 immunogen 20 , 21 . Pfs230 is expressed in both male and female gametocytes without a known membrane anchor and appears on the surface of gametes as a complex with Pfs48/45 22 , a glycosylphosphatidylinositol (GPI) anchored protein 23 .…”
Section: Introductionmentioning
confidence: 99%